Investigation of the Relationship Between Prostate Cancer and MSMB and NCOA4 Genetic Variants and Protein Expression. Issue 1 (4th October 2012) - FitzGerald, Liesel M.; Zhang, Xiaotun; Kolb, Suzanne; Kwon, Erika M.; Liew, Ying Ching; Hurtado‐Coll, Antonio; Knudsen, Beatrice S.; Ostrander, Elaine A.; Stanford, Janet L.
ABSTRACT Two genome‐wide association studies (GWAS) identified the β‐microseminoprotein (MSMB) promoter SNP, rs10993994:C>T, as significantly associated with prostate cancer (PC) risk. Follow‐up studies demonstrate that the variant allele directly affects expression of the MSMB‐encoded protein, PSP94, and also suggest that it affects mRNA expression levels of an adjacent gene, NCOA4, which is involved in androgen receptor transactivation. In a population‐based study of 1, 323 cases and 1, 268 age‐matched controls, we found the NCOA4 SNP, rs7350420:T>C, was associated with a 15% reduction in PC risk, but the association was not significant after adjustment for the rs10993994:C>T genotype. Tumor tissue microarrays of 519 radical prostatectomy patients were used to measure PSP94 and NCOA4 protein expression. Taken together, these data confirm that the rs10993994:C>T variant allele is associated with decreased PSP94 expression, and the association is stronger in tumor compared to normal prostate tissue. No association was observed between rs10993994:C>T and NCOA4 expression, and only moderate associations were seen between two NCOA4 SNPs, rs10761618:T>C and rs7085433:G>A, and NCOA4 protein expression. These data indicate that the increase in PC risk associated with rs10993994:C>T is likely mediated by the variant's effect on PSP94 expression; however, this effect does not extend to NCOA4 in the data presented here.